Gradual Reforms of Capital Income Taxation - Howitt, Peter; Sinn, Hans‐Werner (American Economic Review, 1986)
This paper analyzes the intertemporal allocation effects of anticipated tax rate changes, reconsidering the recommendations of the Meade Committee in a perfect foresight general equilibrium model of economic growth. It is shown that the R-base (or consumption) tax can be more distortionary than an income tax and that a revenue-neutral integration of corporate and personal taxation will lower social welfare. Moreover, it is argued that a dividend tax dominates the R-base tax because it places its distortions on the financial, rather than on the real, side of the economy. Copyright 1989 by American Economic Association.